The Influence of Organizational Support and Family Support on the Entrepreneurial Intentions of Lampung University Students - Putri, Khalisa Almadea; Erlina, Rr. (International Journal Of Education, Social Studies, And Management (IJESSM), 2025)
Entrepreneurial activities are seen as having an important role of driving innovation, creating jobs, and supporting economic growth. The intention to become an entrepreneur is considered the most effective primary indicator for predicting entrepreneurial behavior, which can then developed into entrepreneurial actions. This research examines the influences of organizational support (university) and family support on entrepreneurial intention among students at the University of Lampung. This research aims to determine whatever there is an influence between organizational support (university) on the entrepreneurial intention of student at the Universiyt of Lampung and the influence of family support on the entrepreneurial intention of students at the University of Lampung. In this study, the approach used is a survey through questionnaires given to respondents involving 391 students from the University of Lampung. The research result show that the organizational support (university) has a positive and significant impact on the entrepreneurial intention of students at the University of Lampung, and family support has a positive and significant impact on the entrepreneurial intentions of students at the University of Lampung. Then, this research also suggest that universities should enhance business development support for students, and it is important to note that the economic support provided by families plays a crucial role in determining an individual’s decision to start a business.